Gender differences in relation of students to sports activity - O.Y. Marchenko (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The problem of gender approach in the modern physical education in schools is considered. The experiment was conducted with students of 5-11 grades of secondary schools in the city of Poltava in the amount of 419 people. By the experiment, the students were involved in I-year students (35 girls and 16 boys). It is noted that for the normal socialization are important sex and gender roles. They are associated with the awareness itself as the representative of a particular sex with the norms of behavior, characteristic of members of this sex. Show the direction of consideration for the interests, motivations, values in the process of physical education. Found that to attract students to the sports activity requires consideration of the physiological and morphological and functional characteristics of the individual through the process of gender mainstreaming in the school system.